Clinical performance of metagenomic next-generation sequencing for distinction and diagnosis of Mucorales infection and colonization - Zhou, Xiaoli; Yang, Chenxi; Liu, Xin; Wang, Jiaqiang; Li, Yanqiao; Pan, Lingai; Peng, Shengkun; Yu, Hua; Deng, Xiren (Frontiers in Cellular and Infection Microbiology, 2025)
Mucormycosis is a lethal fungal infection disease with high mortality rate. However, investigations assessing the value of metagenomic next-generation sequencing (mNGS) for distinguishing Mucorales infection from colonization are currently insufficient. A retrospective analysis of clinical date from 71 patients at Sichuan Provincial People’s Hospital from September 2021 to September 2024 was conducted. The performance of mNGS in distinguishing Mucorales infection from colonization, along with the differences in patients’ characteristics, imaging characteristics, antimicrobial adjustment, and microbiota, were examined. Among the 71 patients, 51 were identified as Mucorales infection group (3 proven and 48 probable cases), and 20 were colonization group (possible cases). Receiver operating characteristic (ROC) curve for mNGS indicated an area under the curve of 0.7662 (95%CI: 0.6564-0.8759), with an optimal threshold value of 51 for discriminating Mucorales infection from colonization. The infection group exhibited a higher proportion of antimicrobial adjustments compared to the colonization group (64.71% vs. 35.00%, P < 0.05), with antifungal agent changed being more dominant (43.14% vs. 10.00%, P < 0.01). Mucorales RPTM value, length of hospital stays, hsCRP, immunocompromised, malignant blood tumor, and antifungal changed were significantly positively correlated with Mucorales infection. Rhizomucor pusillus showed significant differences between the two groups. The abundance of Torque teno virus significantly increased in the infection group, whereas the colonization group exhibited higher abundance of Rhizomucor delemar. mNGS is a valuable tool for differentiating colonization from infection of Mucorales. Malignant blood tumor, immunocompromised, length of hospital stays and hsCRP were significant different indicators between patients with Mucorales infection from colonization.